Straight talk to college students on management as a career. - WILEY, CAROLYN (College Student Journal)
Addresses issues in planning a career in management and surviving in that career. Discussion on the career planning stages; Measurement of career success; Future outlook for managers; Survival strategies in management; Enduring equalities for managers; Career opportunities equation.